Effect of ocean oxidation on the chemical structure of marine kerogen. (April 2017) - Longbottom, Todd L.; Hockaday, William C.; Boling, Kenneth S.; Dworkin, Stephen I.
Highlights: Bulk molecular composition of marine kerogens analyzed using 13 C NMR. Redox depositional conditions estimated using trace elemental analysis. Kerogen molecular structure reflects paleo-ocean redox conditions. Oxic depositional conditions favor preservation of aromatic C functionalities. Anoxic conditions favor preservation of alkyl C moieties. Abstract: The burial of organic matter (OM) in marine sediments is an important control on global climate and petroleum formation on geological timescales. While the oxygen exposure time of sediment has been shown to affect the efficiency of organic carbon burial, and influence OM properties in recent sediments, the implications for the chemical composition of kerogen have not been tested. This study tests the hypothesis that oceanic redox conditions are an important control on the molecular structure and composition of kerogen. Samples from a number of outcropping Late Cretaceous mudstones of the Eagle Ford Formation were chosen, spanning a gradient of paleo-redox depositional conditions (oxic/sub-oxic to anoxic) and the bulk molecular composition of the kerogen was determined using solid state 13 C nuclear magnetic resonance (NMR) spectroscopy. The NMR spectral properties of kerogen covaried with redox-sensitive trace metal abundance, whereas the thermal maturity and OM source biomarkers were relatively invariant. Anoxic environments favor the preservation of alkyl C moieties, while kerogen formed in oxic depositional environments was enriched in aromatic C. This study is the first to demonstrate that diagenetic consequences of bottom water redox conditions are retained in the molecular structure of the kerogen macromolecule on geological timescales.